Multi-View Acoustic Field Imaging With Digital Color Holography - Hassad, Saoucene; Ferria, Kouider; Bouamama, Larbi; Picart, Pascal (Frontiers in Photonics, 2022)
This paper proposes an approach for acoustic field imaging using simultaneous multi-view digital holography based on three-color digital off-axis holography. Considering spatio-chromatic multiplexing and the recording with a monochrome sensor, the numerical processing of time-sequences of holograms yields both the amplitude and phase of the acoustic field along three different directions of observation. Distortion analysis is presented and the acousto-optic interaction along the optical beam is discussed using a theoretical modelling. Experimental results with an emitter at 40 kHz establish the proof-of-concept of the proposed multi-view imaging for acoustic fields.